Indonesian Maritime Diplomacy: Realizing the Global Maritime Fulcrum Through IORA - Ulil Amri; M Syaprin Zahidi (Nation State, 2023)
This article discusses the role of maritime diplomacy conducted by Indonesia through the Indian Ocean Rim Association (IOR) in realizing its vision as a Global Maritime Fulcrum. The article presents a descriptive qualitative analysis. We explore maritime diplomacy and international cooperation to understand why Indonesia actively participates in IORA. The discussion reveals that IORA serves as a driving force for Indonesia in advancing its national interest and rebuilding trust in Indonesia's maritime culture.